High‐Performance Electrocatalysts for Oxygen Reduction Derived from Cobalt Porphyrin‐Based Conjugated Mesoporous Polymers. (29th November 2013) - Wu, Zhong‐Shuai; Chen, Long; Liu, Junzhi; Parvez, Khaled; Liang, Haiwei; Shu, Jie; Sachdev, Hermann; Graf, Robert; Feng, Xinliang; Müllen, Klaus
<x xml:space="preserve">Abstract</x> A cobalt‐nitrogen‐doped porous carbon that exhibits a ribbon‐shape morphology, high surface area, mesoporous structure, and high nitrogen and cobalt content is fabricated for high‐performance self‐supported oxygen reduction electrocatalytsts through template‐free pyrolysis of cobalt porphyrin‐based conjugated mesoporous polymer frameworks. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>